Etude des processus de dérive et de sélection liés aux pratiques d'élevage en écloserie d'huître creuse - Boudry, Pierre (2006)
Genetic consequences of production of Pacific oyster larval in hatchery: drift and selective pressures related to rearing practices. In order to study the genetic consequences of production of oyster larvae in hatcheries, two factors were examined: the effects of discarding the smallest larvae (i.e. culling) and temperature effects. A mixed-family approach was used in order to infer the genetic composition of the larval population. The results show that high polymorphic microsatellite-based family assignment is a powerful tool for the study of bivalve larvae genetics. Culling by selective sieving is an advantageous practice at a phenotypic scale, but also represents a substantial risk for diversity loss if parentage assignment is not introduced as a breeding practice. Settlement of slow growing larvae contributes to minimizing the variability of reproductive success and therefore to maximizing genetic diversity. These results corroborate the lower estimations of variability made on broodstocks from French commercial hatcheries relative to natural populations. Temperature exerts an influence on the expression of genetic variability for larval growth. A temperature of 26°C, coupled with culling could amplify the selective effect. Furthermore, selection of fast growing larvae has proven to counteract inbreeding depression at this stage. Genetic effects of intensive rearing conditions are significant and should be taken into account in hatchery practices, especially in terms of genetic diversity management. Afin d'étudier les conséquences génétiques des pratiques de production de larves en écloserie d'huître creuse, deux facteurs ont été examinés : l'effet de l'élimination des plus petites larves et l'effet de la température. Une approche de familles élevées en mélange a été utilisée afin d'avoir accès à l'information génétique au stade larvaire. Les résultats obtenus montrent que l'assignation de parenté basée sur des marqueurs microsatellites hautement discriminants est un outil performant pour les études ...